Integrating Education for Sustainable Development in Tanzanian Ordinary Secondary School Curriculum: Teacher’ Perspectives - Lufunyo Jonas, Konga; Ephrem, Abdon (Journal of Education For Sustainable Innovation, 2025)
This article explores the perspectives of teachers towards integration of Education for Sustainable Development (ESD) in Tanzanian ordinary secondary school curriculum.  Using a qualitative approach and phenomenological design, the study explored teachers’ lived experiences through interviews and observation from 8 selected secondary schools in  the Dodoma City Council. Thematic analysis was used to analyse the collected data. The findings revealed that secondary school teachers are aware of the presense of ESD contents in the curriculum of the subjects they teach and are very supportive of the ESD initiatives beleving that  ESD equip students with skills to protect the environment. However,  their perspectives regarding the integration of ESD into ordinary secondary school curriculum varied across subjects, which suggests that the implementation of education for sustainable development is a contextual and contested field. The significant contribution of this paper is represented by its implications for the implementation of ESD in ordinary secondary schools in Tanzania. Having highlighted the potential of teachers perspectives of education for sustainable development, the curriculum developers can review how education for sustainable development is reflected in the school curricula and address areas that require attention to ensure students acquire comprehensive knowledge, skills and values on education for sustainable development.